Developing an Unbiased Multiplex PCR System to Enrich the TRB Repertoire Toward Accurate Detection in Leukemia - Wu, Jinghua; Wang, Xie; Lin, Liya; Li, Xuemei; Liu, Sixi; Zhang, Wei; Luo, Lihua; Wan, Ziyun; Fang, Mingyan; Zhao, Yi; Wang, Xiaodong; Mai, Huirong; et al. (Frontiers in Immunology, 2020)
Accurate T cell receptor repertoire profiling has provided novel biological and clinical insights in widespread immunological settings, however, there is a lack of reference materials in the community that can be used to calibrate and optimize the various experimental systems in different laboratories. In this study, we designed and synthesized 611 TCR beta chain (TRB) templates and used them as reference materials to optimize the multiplex PCR experimental system to enrich the TRB repertoire. We assessed the stability of the optimized system by repeating the experiments in different batches and by remixing the TRB templates in different ratios. These TRB reference materials could be used as independent positive controls to assess the accuracy of the experimental system, and they can also be used as spike-in materials to calibrate the residual biases of the experimental system. We then used the optimized system to detect the minimal residual disease of T cell acute lymphoblastic leukemia and showed its higher sensitivity compared with flow cytometry. We also interrogated how chemotherapy affected the TCR repertoire of patients with B-cell acute lymphoblastic leukemia. Our result shows that high-avidity T cells, such as those targeting known pathogens, are largely selected during chemotherapy, despite the global immunosuppression. These T cells were stimulated and emerged at the time of induction treatment, and further expanded during consolidation treatment, possibly to fight against infections. These data demonstrate that accurate immune repertoire information can improve our understanding of the adaptive immunity in leukemia and lead to better treatment management of the patients.